Identification of an AKT-dependent signalling pathway that mediates tamoxifen-dependent induction of the pro-metastatic protein anterior gradient-2 - Hrstka, Roman; Murray, Euan; Brychtova, Veronika; Fabian, Pavel; Hupp, Ted R; Vojtesek, Borivoj (Cancer letters, 2013)
The pro-metastatic protein anterior gradient-2 (AGR2) was previously demonstrated as a predictive factor of poor response to tamoxifen treatment. In this study we aimed to delineate the key signalling pathway that may contribute to regulation of AGR2 protein induction in order to identify novel targets to overcome tamoxifen resistance in tumour cells. Together, our data identify PDPK1-AKT as a pro-oncogenic signalling pathway that triggers AGR2 protein induction in response to tamoxifen and suggest that AKT inhibitors could be used as part of a therapeutic strategy to treat tamoxifen resistant, AGR2 over-expressing cancers.
Keywords: 3-Phosphoinositide-Dependent Protein Kinases; nádory prsu; Base Sequence; Female; Proto-Oncogene Proteins c-akt; Mucoproteins; Cell Line, Tumor; tamoxifen; ženské pohlaví; onkogenní proteiny; serin; lidé; Molecular Sequence Data; Breast Neoplasms; Oncogene Proteins; proteinkinasy PDK; signální transdukce; Protein Serine-Threonine Kinases; mukoproteiny; Proteins; Signal Transduction; protoonkogenní proteiny c-akt; ribonukleosidy; proteiny; molekulární sekvence - údaje; Ribonucleosides; mikro RNA; sekvence nukleotidů; Serine; MicroRNAs; Tamoxifen; Antineoplastic Agents, Hormonal; protein-serin-threoninkinasy; hormonální protinádorové látky; nádorové buněčné linie; Humans